Weighting Model of Internal Rating System to Control Non-Performing Loan at. PT. XYZ (Persero) Tbk - Aripradipta, Nieken Sukma; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2012)
The  effectiveness  and  the  efficiency  of  controlling and managing  credit is become the most important things that need to be considered  in bank, due to the function  of bank as an  intermediation   in  collecting  and  disbursement   of  people money and credit become the largest source of income for the corresponding   bank.  PT.  XYZ  (persero)  Tbk  is  the  fourth largest  bank  in  Indonesia.  As  one  financial  institution   that plays an important  role in the economical  sector of Indonesia, XYZ has to maintain the stability of their performance. In maintaining   the   stability   of   their   performance,   PT.   XYZ (Persero)  Tbk  is  completed   with  a  tools  called  as  Internal Rating System (IRS) that could help them in analyzing the feasibility   of  the  potential   debtor   for  the  credit  approval. However,  as the  economy  fluctuation  in Indonesia,  PT.  XYZ (Persero)  Tbk  faces  a problem  related  with  the increment  of the NPL (Non-Performing  Loan). It is due to the errors of the company  in  determining  the  weighted  value  in  IRS.  Where they were giving the same weighting value for a different economical sectors, in fact each economical sector are having a different  risk and characteristics.  This research  would  give a proposed solution for PT. XYZ (Persero) Tbk as alternative solution  that  is new  weighting  model  for  IRS  by considering the characteristics  and risks for each economical sector. Where the  implementation   of  this  new  weighting   model  hopefully could  help  PT.  XYZ  (Persero)  Tbk  in  controlling  their  NPL ratios. Key Words:  Risk Management,  Internal  Rating  System,  IRS, weighting model, banking, credit.